Change in cardiac troponin T level after intravitreal anti-vascular endothelial growth factor treatment: Prospective pilot study. Issue 3 (May 2020) - Rebeiz, Abdallah G; Mahfoud, Ziyad; Abdul Fattah, Maamoun; Saad, Alain; Safar, Ammar; Bashshur, Ziad F
Background: Evaluate subclinical myocardial injury associated with intravitreal anti-vascular endothelial growth factor therapy by measuring serum high-sensitivity cardiac troponin T. Methods: This is a prospective pilot comparative study conducted at American University of Beirut Medical Center, Beirut, Lebanon. In total, 40 consecutive patients were randomized to receive either intravitreal bevacizumab or ranibizumab. Patients received three consecutive monthly injections of the assigned drug, then continued treatment as needed. Systemic concentrations of high-sensitivity cardiac troponin T and vascular endothelial growth factor were obtained at baseline, week 9, and week 24. Primary endpoint measure was change in high-sensitivity cardiac troponin T levels compared to baseline. Secondary endpoint measure was change in systemic vascular endothelial growth factor levels. Results: There was no significant difference in high-sensitivity cardiac troponin T levels over time ( p = 0.227) within each treatment group and no significant difference between treatments at any time point ( p = 0.276). There was a significant decrease in plasma vascular endothelial growth factor levels at week 9 ( p = 0.001) and week 24 ( p < 0.001) compared to baseline. In the ranibizumab group, vascular endothelial growth factor levels were not significantly different at weeks 9 and 24 compared to baseline ( p = 0.708 and p = 0.117, respectively). There was a significant association between the number of bevacizumab injections from weeks 8 to 24 and the decrease in vascular endothelial growth factor levels at week 24 ( R = −0.67, p = 0.032). This correlation was not observed in the ranibizumab group ( R = −0.341, p = 0.141). Conclusion: Repeated intravitreal bevacizumab or ranibizumab did not influence serum high-sensitivity cardiac troponin levels. Intravitreal bevacizumab but not ranibizumab lowered free-systemic vascular endothelial growth factor levels, which was observed in this study to be inversely related to the number of bevacizumab injections.